2010
DOI: 10.5694/j.1326-5377.2010.tb04025.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating apparent variation in quality of care: the critical role of clinician engagement

Abstract: This article reports the experience of the Victorian Department of Health in seeking clinician engagement in the testing of 11 quality‐of‐care indicators in 20 health services in Victoria. The Department previously developed a suite of 18 core indicators and seven subindicators known as the AusPSI set. We used routinely collected administrative data from the Victorian Admitted Episodes Dataset to produce variable life‐adjusted display (VLAD) control charts for 11 selected indicators. The Department recognises … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 5 publications
(6 reference statements)
1
16
0
Order By: Relevance
“…The positive effects of performance measurement often do not materialize because of problems with access to data and insufficient resources for data collection (27,28). Time delays in follow-up undermine clinicians' confidence in data (29,30) and reduce the accountability for outcomes (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive effects of performance measurement often do not materialize because of problems with access to data and insufficient resources for data collection (27,28). Time delays in follow-up undermine clinicians' confidence in data (29,30) and reduce the accountability for outcomes (31).…”
Section: Discussionmentioning
confidence: 99%
“…Performance measurement is a complex task and multiple stakeholders must be convinced of the relevance and motivational power of performance measurement. While health care professionals may be thought of as a homogenous stakeholder group, they often have very different views on quality of care (29). Physicians, for example, tend to concentrate on the outcomes dimension while nurses tend to concentrate on the experience dimension (16,32).…”
Section: Discussionmentioning
confidence: 99%
“…This was in direct comparison to the frontline stakeholders who felt much less engaged, with mean scores ranging from 1.74 to 2.69. Engaging frontline healthcare professionals in quality improvement has been an issue that remains concerning for health systems globally,[2,23,6668] Interestingly, SCN members and support staff who work more peripherally with the SCNs did not differ in their engagement scores, although support staff more often reported that items were not applicable, particularly empower items.…”
Section: Discussionmentioning
confidence: 99%
“…Stakeholder engagement has been described as essential and even “critical” [ 1 3 ] for moving knowledge into action within healthcare [ 4 , 5 ]. Efforts to transform large systems are more successful when healthcare professionals are engaged, resulting in improvements to clinical outcomes and patient safety [ 6 9 ], quality of care [ 8 , 10 , 11 ], and financial performance [ 8 ].…”
Section: Introductionmentioning
confidence: 99%